(3cJGH GdHjGfs - (3CMeO Hf OGhO Hf hffO GdOjfhQj, CHh MfjaI , GdOjfhQj,J (B282 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH GdNGA s
(3BNQgG (B:s
(3jfJgi Edi BNQ HGH GdQGA s
(3GdejcQhajde eXde hZjQ hGVM ai GdJUhjQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B123s
Keywords: (3Gdabg GdMfajs